2007
DOI: 10.1161/atvbaha.107.142638
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Heme Oxygenase-1 in Human Vascular Cells Is Regulated by Peroxisome Proliferator-Activated Receptors

Abstract: Objective-Activation of peroxisome proliferator-activated receptors (PPARs) by lipid-lowering fibrates and insulinsensitizing thiazolidinediones inhibits vascular inflammation, atherosclerosis, and restenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
173
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 206 publications
(184 citation statements)
references
References 60 publications
7
173
4
Order By: Relevance
“…34 However, although PPAR-␥ agonists have been shown previously to restore proangiogenic factors, upregulate HO-1, 10 and increase the production of VEGF in vitro [35][36][37] and in vivo, 18 rosiglitazone failed to alter angiogenic factors in the RUPP rat in the present study. A recent study, involving the induction of HO-1 in RUPP rats via the administration of cobalt (III) protoporphyrin IX chloride, demonstrated that, as a result of cobalt (III) protoporphyrin IX chloride treatment, placental expression of HO-1 was increased, and there was a significant shift in the angiostatic balance ratio (sFlt-1:VEGF).…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations
“…34 However, although PPAR-␥ agonists have been shown previously to restore proangiogenic factors, upregulate HO-1, 10 and increase the production of VEGF in vitro [35][36][37] and in vivo, 18 rosiglitazone failed to alter angiogenic factors in the RUPP rat in the present study. A recent study, involving the induction of HO-1 in RUPP rats via the administration of cobalt (III) protoporphyrin IX chloride, demonstrated that, as a result of cobalt (III) protoporphyrin IX chloride treatment, placental expression of HO-1 was increased, and there was a significant shift in the angiostatic balance ratio (sFlt-1:VEGF).…”
Section: Discussioncontrasting
confidence: 70%
“…Thus, to see a beneficial effect of rosiglitazone on the sFlt-1/VEGF balance (as a consequence of alterations in placental HO-1 expression) it may be necessary to implement treatment at the point of surgical intervention (ie, RUPP surgery on GD14) as per cobalt (III) protoporphyrin IX chloride treatment. However, although rosiglitazone has been shown to upregulate HO-1 expression in both vascular smooth muscle and endothelial cells 10 it failed to do so in lung fibroblasts, 38 which may suggest a cell-specific effect that does not extend to the most abundant placental cell type, the trophoblast. Thus, in the present study, the beneficial effects of rosiglitazone, in terms of both vascular function and blood pressure, may simply be mediated by direct modulation of endothelial HO-1 activity, because these effects were abrogated by the HO-1 activity inhibitor SnPP.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Increase in adiponectin has been shown to improve the beneficial effects of antihypertensive agents in hypertensive patients (19). The peroxisome proliferator-activated receptor (PPAR)␥ response was found to increase expression of adiponectin (20) and also to regulate the expression of heme oxygenase (HO)-1 in human vascular cells (21).…”
mentioning
confidence: 99%